(untitled) (International Journal of Engineering and Computer Science, 2013)
The model of substrate integrated waveguide (SIW) has been analyzed and designed to investigate the effect of geometrical shape on propagation characteristic. Parameters that have been evaluated in this work are electric field, return losses and the transmission gain. Printed circuit board (PCB) is used as dielectrics to evaluate the results in the frequency domain of 6 to 11 GHz. FEM based method is applied to optimize the design of SIW device. The results obtained had shown that gain increases with the increase in frequency upto 9.75 GHz and correspondingly the return loss is minimum at this frequency.